The London Eye mystery - Dowd, Siobhan (Yearling, 2008)
When Ted and Kat's cousin Salim disappears from the London Eye ferris wheel, the two siblings must work together--Ted with his brain that is "wired differently" and impatient Kat--to try to solve the mystery of what happened to Salim.